2002
DOI: 10.1046/j.1432-1033.2002.03049.x
|View full text |Cite
|
Sign up to set email alerts
|

A critical motif for oligomerization and chaperone activity of bacterial α‐heat shock proteins

Abstract: Oligomerization into multimeric complexes is a prerequisite for the chaperone function of almost all α‐crystallin type heat shock proteins (α‐Hsp), but the molecular details of complex assembly are poorly understood. The α‐Hsp proteins from Bradyrhizobium japonicum are suitable bacterial models for structure‐function studies of these ubiquitous stress proteins. They fall into two distinct classes, A and B, display chaperone activity in vitro and form oligomers of ≈ 24 subunits. We constructed 19 derivatives co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
80
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 47 publications
10
80
0
2
Order By: Relevance
“…Of the 10 thermotolerance mutants that were characterized biochemically, all 6 mutations in the ␣-crystallin domain and the C-terminal truncation reduced both the oligomeric stability and the in vitro chaperone activity of Hsp16.6. Previous biochemical studies with a number of different sHsp family members have shown a strong relationship between oligomerization and chaperone activity (29)(30)(31). Furthermore, the correlation between the ability to form oligomers and the ability to confer thermotolerance in vivo has been shown with the L66A and V143A mutants of Hsp16.6, which are dimeric.…”
Section: Discussionmentioning
confidence: 92%
“…Of the 10 thermotolerance mutants that were characterized biochemically, all 6 mutations in the ␣-crystallin domain and the C-terminal truncation reduced both the oligomeric stability and the in vitro chaperone activity of Hsp16.6. Previous biochemical studies with a number of different sHsp family members have shown a strong relationship between oligomerization and chaperone activity (29)(30)(31). Furthermore, the correlation between the ability to form oligomers and the ability to confer thermotolerance in vivo has been shown with the L66A and V143A mutants of Hsp16.6, which are dimeric.…”
Section: Discussionmentioning
confidence: 92%
“…The N-terminal regions in ␣A-crystallin, ␣B-crystallin, Hsp18.1, and Hsp16.9 were all proposed to be putative substrate-binding sites as revealed via hydrogendeuterium exchange, bis-ANS photoincorporation analyses, and crystal structure examination (6,12,47,48). Assuming that such a substrate binding role is true for the N-terminal regions in all sHSPs, then the failure of the N-terminal deletion mutants to exhibit chaperone-like activities for C. elegans Hsp16 -2 and the sHSPs from B. japonicum might be explained as reflecting the involvement of this region in substrate binding, rather than the necessity for the formation of large oligomers (26,37). Likewise, the lack of chaperone-like activities for a few sHSPs found in C. elegans (Hsp12.6, Hsp12.2, and Hsp12.3), naturally existing as either monomers, dimers, or tetramers, is probably caused by the shortening of their Nterminal regions, which would not be able to act as binding sites for denaturing substrate proteins, instead of the failure of the formation of large oligomers (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus conceivable that, during evolution, the Hsp16.3 trimers were formed from a dimer prototype as a result of the structural information contributed by its N-terminal region and the Cterminal extension. The variation in these two end regions has indeed been suggested to contribute to the diversity of the oligomers (as in shape, size, dynamics) formed for various sHSPs (12,18,19,22,26,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These residues bind to hydrophobic patches on other proteins and are central to the formation of oligomers as well as sHSP-substrate complexes. As a consequence, truncations of the N-terminal arm affect both the oligomer assembly and chaperone activity of many sHSPs (Studer et al 2002;Sun and MacRae 2005). A study of the sHSP AgsA from Salmonella enterica demonstrated that truncations of different lengths at its termini resulted in drastic differences in the oligomeric state, which ranged from dimers to 22-mers.…”
Section: Introductionmentioning
confidence: 99%